A cross-sectional study of the impact of physiotherapy and self directed exercise on the functional outcome of internally fixed isolated unimalleolar Weber B ankle fractures. Issue 2 (February 2017) - Karam, E.; Shivji, F.S.; Bhattacharya, A.; Bryson, D.J.; Forward, D.P.; Scammell, B.E.; Ollivere, B.J.
Abstract: This study aimed to measure the functional outcome and quality of life in a group of patients with the same fracture type (unimalleolar Weber B ankle fractures) treated operatively at various time points and to explore the determinants of such outcomes. A cross-sectional retrospective population study was conducted. Validated Patient Related Outcome Measures (PROMs) and patient interviews were used. Fifty-one patients were included with a mean age of 54.9 years. Mean follow-up was 25 months (range 4–46 months). Mean functional scores were high (mean AOFAS 79.2, O&M 75.7, VAS-FA 80.5). However, 32% of patients did not classify themselves as fully recovered during interviews. Patient reported self-directed exercise had a statistically significant positive effect on self-reported patient perceptions of outcome (p = 0.022) and PROMs (AOFAS p = 0.01, O&M p = 0.016, VAS-FA p = 0.011). Formal physiotherapy rehabilitation was found to have no effect on self-reported patient perceptions (p = 0.242) or PROMs (AOFAS p = 0.8, O&M p = 0.73, VAS-FA p = 0.46). Our finding that physical activity is associated with improved outcome would suggest structured exercise programmes should be considered in place of physiotherapy to optimise patient outcomes.